Bioremediation of Mercury- Polluted Water in Free Water Surface-Constructed Wetland System by Euglena sp. and Echinodorus palifolius (Nees & Mart.) J.F. Macbr. - Siswanti, Dwi Umi; Daryono, Budi Setiadi; Petrus, Himawan Tri Bayu Murti; Suyono, Eko Agus (Universitas Gadjah Mada, 2023)
Mercury accumulation in the aquatic environment can be highly harmful. The body takes mercury vapor through the lungs, then absorbs mercury metal through the digestive system, and then the blood carries the metal to the brain. Bioremediation is the process of breaking down or converting harmful compounds into non-toxic forms, which can be accomplished through phytoremediation or phycoremediation. The goal of this study was to examine the growth and anatomy of Euglena sp. after being cultured in the mercury-containing FWS-CW waste treatment system. The ability of Euglena sp. and Echinodorus palifolius to bioremediate mercury at different concentration as well as association and non-association treatments. This study was carried out in a bioreactor known as FSW-CW (Free Water Surface-Constructed Wetlands). Plant growth (plant height and number of leaves), chlorophyll content, diameter of root and petiole, metaxylem diameter of root, petiole, and leaves, cortical thickness of root and leaves, and petiole anatomy were all measured. Water temperature, pH, salinity, and light intensity were all measured as environmental parameters. Mercury treatment reduced Euglena density (183.5 cells. mL-1103 in control and 12.6 cells. mL-1103 in 100 ppm mercury treatment) and number of E. palifolius leaves, but not plant height and chlorophyll. Root and petiole diameters were affected by the mercury treatment, petiole diameter decreased unless the concentration was 100 ppm, whereas root diameter actually increased. The diameter of the root metaxylem increased, but the petioles and leaves, as well as the thickness of the root cortex, did not provide a significant response. The growth of E. palifolius was still optimal in the presence of Euglena in mercury-containing medium.